Sistem pakar mendeteksi gangguan emosional menggunakan forward dan backward chaining - alif sultan (Politeknik Ganesha Medan, 2023)
Mental health conditions in Indonesia are increasing due to lack of attention to one's own mental health, including emotional disorders which are included in mental disorders. Most Indonesians are not aware of and ignore the symptoms that lead to emotional disturbances, even though mental health is as important as physical health. Therefore it is necessary to have an expert system to diagnose emotional disorders in order to help detect emotional disorders and provide initial advice on handling emotional disorders suffered. In this study, according to the referrals provided by experts on mental health disorders, it consists of 5 categories, namely hypochondriasis, paranoia, psychopaths, schizophrenia, hypomania and the system will provide initial advice on handling the emotional disorders suffered. This system uses the forward chaining method with backward chaining to determine the diagnosis of emotional disorders as well as providing early treatment advice in the form of prevention to anticipate the worsening mental health condition that is being experienced. The results of this study with 30 test data that have been tested on the system, the system provides results in the form of an early diagnosis of emotional disorders along with initial advice on prevention with an accuracy rate of 86,6 %.